Referencing in a Second Language: Korean EFL Learners' Cohesive Use of References in Written Narrative Discourse - Kang, Jennifer Yusun (Discourse processes, 2009)
This study examined Korean English as a foreign language (EFL) learners' ability to establish textual cohesion in English through appropriate selection of reference forms and reference management strategies in their written narrative discourse. It employed both quantitative and qualitative analysis to explore how the language-specific reference choices and strategies in their first language (L1) may be evident in their second language (L2) discourse production. Participants were Korean adult EFL learners and American native English speakers (NES) in college. Findings from the quantitative analysis of the written narratives showed that the specifically Korean referential strategies of heavily relying on nominals were not evident in the Korean EFL learners' English narrative discourse. However, a closer look at the data with a qualitative approach revealed that the Korean EFL learners' referential strategies were very different from those of the NES. More specifically, the qualitative analysis revealed that, unlike the NES who alternated the use of noun phrases and pronouns strategically to achieve certain discourse effects, the Korean participants did not display such sophisticated use of reference forms within an extended L2 discourse. The findings are attributed to the L1-specific reference management conventions and to the L2 learners' lack of practice and competence in referential strategies at the discourse level.